(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Siddha medicine is one of the oldest medical systems in the world. This system is most commonly practicing in India especially in southern regions. Siddha medicines become popular nowadays because of various outbreaks of communicable and very infectious diseases like chikungunya, dengue, swine flu etc. These diseases of viral origin are very challenge to the modern world because of lack of ideal anti-viral therapy. Pandemic flu is different from ordinary flu because it’s a new flu virus that appears in humans and spreads very quickly from person to person worldwide. Because it’s a new virus, no one will have immunity to it and everyone could be at risk of catching it. This includes healthy adults as well as older people, young children and those with existing medical conditions. The polyherbal decoction Kapa Sura Kudineer (KSK) is a well-known one in this series next to Nilavembu kudineer (NVK). This KSK is introduced for the prevention and the management of Swine flu. And the people of Tamil Nadu are very attentive about this Siddha drug KSK because to prevent and protect from the deadly life threatening disease, Swine flu. Here, an attempt has been made to review the explored ethno pharmacological activities of the ingredients of KSK to strengthen the scientific facts favoring this formulation.